ENGLISH AT HIGHER EDUCATION LEVEL: A NEED ANALYSIS - Tantry Ajeng Parnawati; Atik Ulinuha (Premise: Journal of English Education and Applied Linguistics, 2019)
This study aimed to reveal students’ skills on each English language skill and find out what students need and want on English language learning at higher education level. To meet the aim of the study, a mixed-method approach was employed. The participants of this study were students who have enrolled in a General English course at the target University. Quantitative data was gained from an online questionnaire and Qualitative data was obtained from the interviews. The result of this study showed that students are more confident with their reading and writing skills than their speaking and listening skills. The finding also showed that they need to learn more about speaking skill. For the students’ need, English for supporting their job gained the highest percentage among the other choices. However, students also wanted to learn more on grammar. Therefore, an adjustment for English teaching material at higher education level at the target university needs to conduct